Rice OsSIPK: A central component of ozone-triggered physiological responses - Cho, Kyoungwon (Landes Bioscience, 2009)
The OsSIPK expression is transcriptionally regulated in time and space by diverse environmental stresses and phytohormones.1 Rice OsSIPK and its orthologs in other plants are highly conserved and appear to have overlapping physiological responses.2 Given our interest in understanding the signaling and metabolic pathways responsible for environmental factors, we briefly discuss the role of OsSIPK in ozone-triggered physiological responses, particularly in rice. We also provide evidence on tight correlation between ozone-induced OsSIPK expression and ethylene production.